FinTech projects and initial coin offerings: a research note - Moro, Andrea; Wang, Dao (Pepperdine University, Graziado School of Business and Management, 2019)
We explore the determinants of success of Initial Coin Offerings (ICO) defined as whether the ICO was successful in raising the funds. We look at financial and technical information disclosed by the ICO as well as the information disclosed by third parties about the ICO and the level of legal protection granted. We discover that even if both hard information (financial and technical) and soft information (social media and legal protection) matter, nevertheless a more relevant role is played by the technical information. Based on our analysis, we identify areas that need further investigation in the context of ICOs.
Keywords: Initial Coin Offerings; Blockchain; Start Up finance